Opuntia ficus-indica (L.) Miller fruit from Portugal: alternative crops and food security - Gomes, A. (2019)
The search for plant species to develop sustainable agriculture is nowadays a challenge. Opuntias (cactus), once invasive species, are now part of the natural landscape and the agricultural systems of many regions. Opuntia products (palm, flowers and fruits) are used for food, forage, energy, folk medicine, cosmetic and agronomic purposes, contributing to the food security.